Use of F-18 FDG PET/CT Through Delayed Diuretic Imaging for Preoperative Evaluation of Upper Urinary Tract-Occupying Lesions - Wang, Jun; Zhang, Liang; Wu, Jian Guo; Chen, Ruohua; Shen, Jia lin (Frontiers in Oncology, 2021)
Purpose: To evaluate the value of F-18 FDG PET/CT in the differentiation of malignant and benign upper urinary tract-occupying lesions. Patients and Methods: 64 patients with upper urinary tract-occupying lesions underwent F-18 FDG PET/CT at RenJi Hospital from January 2015 to February 2019 in this retrospective study. Of the 64 patients, 50 patients received nephroureterectomy or partial ureterectomy; 14 patients received ureteroscopy and biopsy. The comparisons of PET/CT parameters and clinical characteristics between malignant and benign upper urinary tract-occupying lesions were investigated. Results: Of the 64 patients, 49 were found to have malignant tumors. Receiver operating characteristic analysis determined the lesion SUVmax value of 6.75 as the threshold for predicting malignant tumors. There were significant associations between malignant and benign upper urinary tract-occupying lesions and SUVmax of lesion (P＜0.001), lesion size (P＜0.001), and patient age (P=0.011). Multivariate analysis showed that SUVmax of lesion (P=0.042) and patient age (P=0.009) as independent predictors for differentiation of malignant from benign upper urinary tract-occupying lesions. There was a significant difference in tumor size between the positive (SUVmax >6.75) and negative (SUVmax ≤6.75) PET groups in 38 of the 49 patients with malignant tumors. Conclusion: The SUVmax of lesion and patient age is associated with the nature of upper urinary tract-occupying lesions. F-18 FDG PET/CT may be useful to distinguish between malignant and benign upper urinary tract-occupying lesions and determine a suitable therapeutic strategy.